2011
DOI: 10.1111/j.1574-695x.2011.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the IL-10/IL-12 axis in human dendritic cells with probiotic bacteria

Abstract: In this study, we have used monocyte-derived dendritic cells (DCs) to design a screening model for the selection of microorganisms with the ability to suppress DC-secreted IL-12p70, a critical cytokine for the induction of T-helper cell type 1 immune responses under inflammatory conditions. By the treatment of DCs with cocktails containing TLR agonists and proinflammatory cytokines, the cells increased the secretion of the Th1-promoting cytokine IL-12p70. Clinically used probiotics were tested for their IL-10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…Several probiotic bacteria, such as LAB, are known to affect the functionality of dendritic cells (DC) in culture (Gad et al, 2011). Modulatory effects on DC have been postulated as a critical mechanism for probiotic-mediated immune modulation (Amar et al, 2015;Dongarrà et al, 2013;Fong, Kirjavainen, Wong, & El-Nezami, 2015;Fong, Shah, Kirjavainen, & El-Nezami, 2015;Martínez-Abad et al, 2016;Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several probiotic bacteria, such as LAB, are known to affect the functionality of dendritic cells (DC) in culture (Gad et al, 2011). Modulatory effects on DC have been postulated as a critical mechanism for probiotic-mediated immune modulation (Amar et al, 2015;Dongarrà et al, 2013;Fong, Kirjavainen, Wong, & El-Nezami, 2015;Fong, Shah, Kirjavainen, & El-Nezami, 2015;Martínez-Abad et al, 2016;Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have confirmed this immunomodulatory effect of Lactobacillus, showing that it leads to augmentation of IL-10 levels [129,132,133] and to a reduction of pro-inflammatory cytokines such as IL-6 and TNF-α [134] . Other probiotics are able to inhibit NF-κB, such as L. plantarum, suggesting that it induces tolerance to food antigens [135] .…”
Section: Probiotics: Epithelium Immune Responses and Therapeuticsmentioning
confidence: 70%
“…As shown in Fig 6 C, the secretion of inflammatory cytokine IL-12p70 was suppressed by OVA/RA NPs comparing with the non-treated immature DC 2.4, while the secretion of anti-inflammatory cytokines IL-10 and TGF-β was kept unchanged. As a result, ratio of expression of IL-10/IL-12p70, which is used as a measure of anti-inflammatory response of cells, [28][29][30] was raised by OVA/RA NPs (Fig. 6 D).…”
Section: Induction Of Semimature Dcs By Ova/ra Npsmentioning
confidence: 99%